Entre o trabalho e a correção: escravas e forras na cadeia de Rio Grande/RS (1864-1875) - Molet, Claudia Daiane Garcia (2011)
This dissertation analyzes the women slave and free workers arrested in the jail of the city of Rio Grande between 1864 and 1875. At this time, these women were inserted in an incipient urban space, mainly characterized by the presence of maritime workers and commerce men. The poor women, especially the African descents ones, needed work to obtain money in order to guarantee the survival of themselves and their families. This way, their behaviors did not fit into the ideal woman concept the bourgeois society had. The research was made from two books of arrestments records in the jail of the city of Rio Grande, which contain the incarcerations of both slave and free women (including the emancipated ones). From the data collected, it was possible to notice that the slave ones were arrested by demand of their master. Regarding the free ones, the reasons were mostly related to drinking, disturbing and walking around in inappropriate times . Most of the women prisoners were black or brown. There was a minority of white women arrested, among which Germans, Portugueses and Uruguayans. Facing this situation, it was evident that the Rio Grande Jail, during the Empire period, was a place of punishment of black and brown poor women who presented behavior considered of disorder by the authorities